Biomarkers for personalised treatment in psychiatric diseases. (September 2013) - Bagdy, Gyorgy; Juhasz, Gabriella
Abstract : Biomarker research of psychiatric disorders is delayed by symptom pattern-related diagnostic categories that are only distantly associated with biological mechanisms. In neuropsychiatric disorders that have high heritability (schizophrenia, autism, Alzheimer's disease), genomic research led to significant genome-wide association study (GWAS) results by increasing the number of subjects in case–control studies, and thus provided new hypotheses regarding the aetiology of these disorders and possible targets for research of new treatment approaches. In contrast, in moderately heritable psychiatric disorders (anxiety disorders, unipolar major depression), the development of symptoms, in addition to risk genes, is more dependent on the presence of specific environmental risk factors. Thus, controlling for heterogeneity, and not simply increasing the number of subjects, is crucial for further significant psychiatric GWAS findings that warrant the collection of more detailed individual phenotypic data and information about relevant previous environmental exposures. Gene–gene interactions (epistasis) and intermediate phenotypes or psychiatric and somatic co-morbidities, by identifying similar cases within a diagnostic category, could further increase the generally weak effects of individual genes that limit their usefulness as biomarkers. In conclusion, we argue that methods that are suitable to identify biologically more homogeneous subgroups within a given psychiatric disorder are necessary to advance biomarker research.